1998
DOI: 10.1021/bp9800182
|View full text |Cite
|
Sign up to set email alerts
|

Technique for the Kinetic Characterization of the Metabolic Reactions of Hepatocytes in Adhesion Culture

Abstract: In this paper, we report on the development of a technique for the kinetic characterization of the metabolic reactions of liver cells in adhesion culture. The technique is based on the use of a continuous-flow bioreactor which is designed and operated in such a way as to ensure a uniform distribution of metabolite at the cell site: hence, the metabolite concentration at the surface of cells cultured in adhesion at the bottom of the bioreactor equals that in the stream leaving the bioreactor. Under steady condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…3) or pyruvate and ammonia (50 min perfusion time in Fig. In hepatocytes, ammonia uptake and urea production have also been found to obey apparent Michaelis-Menten kinetics with respect to the extracellular ammonia concentrations (10). 3 and 4).…”
Section: Discussionmentioning
confidence: 80%
“…3) or pyruvate and ammonia (50 min perfusion time in Fig. In hepatocytes, ammonia uptake and urea production have also been found to obey apparent Michaelis-Menten kinetics with respect to the extracellular ammonia concentrations (10). 3 and 4).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies reported that oxygen uptake rate of primary hepatocytes was critical in the early stage of cell attachment process. 35,36 Various continuous flow and perfusion culture systems were utilized to overcome the mass transfer limitations occurred in the cell/scaffold constructs. [37][38][39] The perfusion culture system, facilitating supply of nutrients and oxygen to the seeded cells and removal of metabolic products and degradation products from biodegradable scaffolds, showed improved cell viability and functions for various tissue regenerations.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, a lower O 2 consumption may be expected as the specific O 2 uptake rate per cell is reported to decrease at increasing cell densities 30. On the other hand, O 2 consumption may rise significantly when a metabolic load is applied to the cells 4. As such, the proposed consumption characteristics are justified by assuming these values to represent the most limiting case for oxygen availability.…”
Section: Methodsmentioning
confidence: 99%